Nurses' Knowledge of CPR as First Responders to the Code Blue System: an Internal Survey at the Manambai Hospital, West Nusa Tenggara Province - Hendri Purwadi; Harmili Harmili; Meri Afridayani (STIKES Adi Husada, 2023)
An in-hospital cardiac arrest (IHCA) is handled by a code blue team. A nurse, then calls the first responder, who discovers a patient having a cardiac arrest must perform CPR while waiting for the code blue team to arrive. Nurses who serve as first responders in Code Blue systems have not been surveyed or studied previously regarding their knowledge of CPR. This study aims to assess the level of knowledge regarding CPR among Nurses as First Responders of the Code Blue system in Manambai Hospital, NTB. The study was a descriptive quantitative with a cross-sectional approach. Eighty-two nurses from the non-critical ward of Manambai Hospital answered questionnaires regarding characteristics and CPR from June to September 2023. The CPR questions consist of eleven multiple-choice choices derived from AHA 2020 guidelines. An analysis of the data was conducted using frequencies and chi-square. A majority of respondents have poor levels of knowledge, accounting for 73. 2%, while good levels of knowledge account for only 26,8%. CPR knowledge is associated with CPR experience with a p-value of p<0.000. Knowledge is a major factor in motivating an individual to take action on CPR in code blue system. Survival rates for individuals suffering a cardiac arrest will decrease by 7-10% every minute if CPR is not performed. Hence, courses and simulations are important tools for increasing the level of knowledge and skills of CPR.